Mathematical models of reliability parameters for complicated power systems - Sydor, A.R.; Teslyuk, V.M. (Технічна електродинаміка, 2012)
A method of investigation of reliability parameters for complicated power systems by means of generating functions is developed taking account of aging of the system’s output elements. Main time parameters for reliability evaluation are examined in this paper. Mathematical models in the form of analytical expressions are worked out for the average duration of the system’s stay in each of its states and for the average duration of the system’s stay in the prescribed availability condition provided that the lifetime of ageing output elements is circumscribed by the Rayleigh distribution.